Two men holding open the book 'Look, Governor' (1977)
Two men hold open the book 'Look, Governor' which was put together by the Associated Students Cal Poly San Luis Obispo. ASI President Ole Meland stands at right. The two stand on the present site of the Robert E. Kennedy Library. The book's purpose was to lobby for a new library on campus. Signatures are present on the pages.